A Study of Various Problems of Physically Handicapped - Sinha, Kumari Bharti (International Journal of Advanced Research in Peace, Harmony and Education; Vol 4 (2019): International Journal of Advance Research in Peace, Harmony and Education, 2019)
Adolescence period is full of stresses and strains. One major problem of adolescents is to be independent of their parants. According to Kiskar [1982], the most destructive and stress-provoking situation is a growing need for independence. It is evident that adolescent boys and girls often make efforts to achieve some degree of freedom from their parents directly or indirectly. This effort may lead to such common symptom of adjustment difficulties as truancy, vagrancy, stealing and sexual misbehaviour. Studies have shown that some of the problems of adolescents are the extensions of those of childhood while others are the anticipations of the adulthood. However, some problems of adolescents are unique to this developmental and transitory period itself. Behavioural scientists have explained the problems of the adolescents under more or less these broader connotations. Personal Data Sheet and Youth Problem Inventory were administrated to 81 physically handicapped and 81 normal respondents to examine whether the two groups differ significantly in terms of their problems relating to family, school, sexual, personal and overall problems. It was hypothesized that there will be significant effect of physical disadvantage over various problems of the respondents. The result revealed that the physical disadvantage showed a significant effect on various problems under study of respondents, namely family school / college, social, personal and overall problems. How to cite this article:  Sinha KB. A Study of Various Problems of Physically Handicapped. Int J Adv Res Peace Harm Edu 2019; 4: 3-6. DOI: https://doi.org/10.24321/2455.9326.201901